NATIONAL AND CULTURAL FEATURES OF COMPUTER JARGONG (sociolinguistic approach) - Shamieva, Nargiza (Foreign Languages ​​in Uzbekistan (JOURNALFLEDU.COM), 2023)
The following work attempts to determine whether students' proficiency in English and its culture influenced their intuitive understanding of computer concepts, that is, whether there was a conversion, similar to SLA, of languages the student knows to visual languages, that is. Knowledge of computer concepts, which is regarded as the transition from Language to Computer Science (LCS). A survey, designed to test students' visual understanding of central concepts in computer scienceis presented. The test should be used by students who have little knowledge of computers, so the understanding they show on the test is due to their understanding of words based on their language training. The presence of term words in the text is noticeably reduced, while the role of multicomponent terminology is significantly increased. The predominance of the role of multicomponent terminology in modern terminologies is explained by the fact that there is a need to nominate complex compound concepts, clarify professional objects and concepts. Hence, their essence is known and new aspects of the studied phenomena are discovered. Moreover, multicomponent terminology not only names and differentiates the emerging concepts, but also systematizes the paradigmatic relations between them, reflecting the system connections of units of a particular terminological system.
Keywords: social communication; computer jargon; internet slang; lexical sub-language; Uzbek culture and association with English